PERANCANGAN ANTARMUKA APLIKASI MOBILE UNTUK MENINGKATKAN AKSES LAYANAN PERBANKAN BPR SARASWATI EKA BUMI - Raihan Akbar Maulana; I Wayan Santiyasa; Luh Gede Astuti (Jurnal Pengabdian Informatika, 2026)
Easy and efficient access to banking services is essential for customers in the digital era, including those of rural banks such as BPR. BPR Saraswati Eka Bumi currently does not offer a mobile banking application, causing customers to rely on manual processes for opening accounts, saving, applying for loans, and placing deposits. In response to this issue, a mobile application interface was designed to support the digital transformation of BPR Saraswati Eka Bumi's services. The design process adopted the design thinking method, consisting of five stages: empathize, define, ideate, prototype, and test. Through these stages, key features were developed including online account registration, SiMaPan savings, loan application, and digital deposit services. The resulting interface prototype was tested internally and received positive feedback regarding its usability and clarity. This design is expected to serve as a reference for the future development of BPR Saraswati Eka Bumi’s official mobile banking application.